Book Review: Waqf and Economy - Rahman, Fathan Aulia (International Journal of Waqf, 2024)
The book ‘Vakıf ve İktisat’ was compiled by a team from the Turkish Directorate General of Foundations to reintroduce the role of waqf in the socio-economic life of Turkish society and the Islamic world. Originating from exhibitions and seminars held since 2006, the book was specifically conceived following a proposal in 2014 by the Turkish Deputy Prime Minister, Bülent Arınç, to display waqf archives related to the economy. This work consists of two main parts: a collection of archives on the management of waqf related to economic activities and visual documentation of waqf properties. The selected archives include vakfiye (waqf deeds), administrative records, fodula defterleri (records of food consumption and distribution in imarets), kesif ve tamir belgesi (documents for the inspection and repair of waqf assets), as well as documents on istibdal and istikraz (conversion of waqf assets and loan records). Through these archives, the book asserts that waqf is not only of spiritual and social value but also served as a crucial instrument in supporting the economy, trade, and the equitable distribution of welfare during the Seljuk and Ottoman eras. Overall, this book is an important contribution to the study of waqf history and Islamic economics, serving as a valuable primary source for researchers wishing to explore the dynamics of waqf management in both historical and contemporary contexts.